IMPLEMENTATION OF THE CLASSDOJO PLATFORM AS E-LEARNING MEDIA AT THE KHALIFAH ISLAMIC ELEMENTARY SCHOOL PALU - Saepudin Mashuri; Rosmayanti; Djaid Ahmad (Paedagogia: Jurnal Pendidikan, 2022)
This study is related to the application of information and communication technology in the field of education, namely the use of digital learning media classdojo in elementary school. This research focuses on how to implement calassdojo as an e-learning medium at the Islamic Elementary School of the Khalifah Palu? Its aim is to reveal the application of classdojo as e-learning platform to digitally shape and monitor behavior and achievement of students in learning. This research uses a qualitative method with a case study approach through data collection techniques; namely: interviews, observations and documentation. The findings of this research indicate that the process of applying classdojo in the learning process for the first class students at Islamic Elementary School of the Khalifah Palu is running well according to the operational standards of this application. The indicators are reflected in students' proficiency in using the classdojo application while participating in e-learning with digital communication tools, such as: undroid, tablet, and account. In addition, through the classdojo application, teachers and parents can control learning activities, behavior and students’ achievements directly on the feature menu that has been made at the planning stage. The use of the classdojo platform received positive responses from teachers, students and parents as well as reflecting the digital literacy culture of students at the Islamic Elementary School of the Khalifah Palu.